Analisis Penggunaan Media PowerPoint dalam Pembelajaran Daring Mata Pelajaran IPS Ekonomi Kelas VII di SMP Hang Tuah Ambon - Dorina Kofit; Franklin William Ubra; Amjad Salong (Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the use of PowerPoint media in online learning for the subject of Social Studies (Economics) in Grade VII at SMP Hang Tuah Ambon. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The findings indicate that PowerPoint assists teachers in delivering material visually and systematically, and it enhances student engagement in online learning. However, several challenges were identified, including limited internet connectivity, inadequate student devices, and insufficient teacher training in presentation design. These findings highlight the importance of educational technology training and infrastructure support to improve the effectiveness of online learning media. This research contributes to the understanding of visual media use in online education, particularly in regions with limited educational resources